Evaluation Of Conventional Digital Camera Scenes For Thematic Information Extraction. - Lim, H.S.; M Jafri, M.Z.; Abdullah, K (2003)
The increasing availability of remote-sensing images, acquired periodically by satellite sensors on the same geo makes it extremely interesting to develop the monitoring systems capable of automatically producing and reg landcover maps of the considered site (Bruzzone, et ai., 2002).